The Influence of Education and Training on Work Performance of Civil Servants at the Population Service Office and Civil Registration of West Seram - Paais, Maartje (jfpublisher, 2022)
The process of organizing teaching and learning in order to improve the knowledge and skills of civil servants through training is very important in order for them to have competencies in accordance with the requirements of each position. Therefore, this research aims to determine the influence of education; training; and both training and education on the performance of civil servants at the Population Service Office and Civil Registration of West Seram. This research used multiple linear regression analysis as its method with primary data in the form of questionnaires to 35 respondents selected and analyzed through interview techniques. Meanwhile, secondary data is obtained from literature reviews that are in accordance with the research topic. The results of this research indicate that (1) education and training simultaneously have a significant influence on the performance of civil servants; (2) education partially has a significant influence on the performance of civil servants; (3) training partially has a significant influence on the performance of civil servants; and (4) the variety of employee performance based on education and training has an effect of 79.6% while the remaining 20.4% is not explained by other variables that are not analyzed, such as job stress factors, work environment, and others.